Sphingolipid rheostat alterations related to transformation can be exploited for specific induction of lysosomal cell death in murine and human glioma - Mora Rodríguez, Rodrigo; Dokić, Ivana; Kees, Tim Steffen; Hüber, Christian M.; Keitel, Denise; Geibig, Renate; Brügge, Britta; Zentgraf, Hanswalter; Brady, Nathan; Régnier-Vigouroux, Anne (Glia, 2010)
The search for cancer cell-specific targets suffers from a lack of integrative approaches that take into account the relative contributions of several mechanisms or pathways involved in cell death. A systematic experimental and computational comparison of murine glioma cells with astrocytes, their nontransformed counterparts, identified differences in the sphingolipid (SL) rheostat linked to an increased lysosomal instability in glioma cells. In vitro and in silico analyses indicate that sphingosine metabolized in lysosomes was preferentially recycled into ceramide, the prodeath member of the rheostat, in astrocytes. In glioma cells, it preferentially was used for production of the prosurvival sphingosine-1-phosphate (S1P). A combination of tumor necrosis factor alpha (TNF-α), lipopolysaccharide (LPS), and interferon gamma (IFN-γ) strongly decreased S1P production that resulted in abnormal lysosome enlargement and cell death associated with mitochondrial dysfunction of glioma cells only. Lack of intracellular S1P in glioma cells was concomitant with protein and lipid accumulation in enlarged lysosomes, indicating a blockade in lysosome recycling, and hence a role for S1P in membrane trafficking. A pharmacological sphingosine kinase inhibitor efficiently replaced the TNF-α, LPS, and IFN-γ combination and killed murine and human glioma cells without affecting astrocytes. Our study provides evidence for a novel mechanism of lysosomal death dependent upon the SL rheostat that can be specifically triggered in glioma cells. It further strengthens the potential of cancer therapies based on specific ceramide pathway alterations. © 2010 Wiley-Liss, Inc.
Gesehen am 03.05.2023